PENGARUH PRAKTIK KERJA LAPANGAN, LINGKUNGAN KELUARGA, DAN MOTIVASI MEMASUKI DUNIA KERJA TERHADAP KESIAPAN KERJA SISWA KELAS XII JURUSAN PEMASARAN SMK SWASTA JAMBI MEDAN - Intan Riang Buulolo; Dita Eka Pertiwi Sirait (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to investigate the influence of Internship, Family Environment, and Motivation to Enter the Workforce on the Work Readiness of Grade XII Marketing students at SMK Swasta Jambi Medan.The research was conducted at SMK Swasta Jambi Medan with a total of 74 Grade XII Marketing students as participants, selected through total sampling. This study employed a quantitative approach, and data were collected using structured questionnaires.The results of the multiple linear regression analysis reveal that Internship has a positive and significant effect on students’ work readiness (t = 5.942 > 1.994; p = 0.000 < 0.05), Family Environment (t = 5.956 > 1.994; p = 0.000 < 0.05), and Motivation to Enter the Workforce (t = 5.469 > 1.994; p = 0.000 < 0.05). Simultaneously, these three variables significantly influence work readiness (F = 60.141 > 2.74; p = 0.000 < 0.05). The coefficient of determination (R² = 0.720) indicates that 72% of the variance in students’ work readiness is explained by these independent variables, while the remaining 28% is attributed to other factors beyond this study.These findings underscore the critical role of internship experiences, a supportive family environment, and personal motivation in developing students’ work readiness. The study also provides practical implications for schools, parents, and students to continuously enhance these factors to better prepare students for the demands of the workforce.